Comprehensive Analysis of the Stages in the Logistics Chain for Aromatic and Medicinal Plants (PAM) in Northern Morocco - CHBANI Kaoutar; BOUARFA Jaouad (African Scientific Journal, 2024)
Abstract This This paper provides a detailed examination of the critical logistic stages of aromatic and medicinal plants (PAM) in northern Morocco. By adopting a qualitative methodological approach based on case studies and interviews with key stakeholders in the supply chain, each stage from the research phase to the commercialization phase was scrutinized to identify aspects that may hinder total supply chain optimization. The major problems identified include barriers to accessing scientific information, insufficient funding for primary research, seasonal variations, and differences in the quality of raw materials delivered. To address these issues and achieve optimal supply chain configuration, the proposed solutions include the improvement of utilized databases, active management of growing seasons, and investment in transportation infrastructure. The main conclusions indicate that addressing these challenges would optimize the PAM supply chain, contributing to the sustainable and profitable development of this important sector in the Moroccan economy. Keywords: Aromatic and medicinal plants (PAM), Supply chain, Supply, Quality of raw materials, Transformation.